PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI 25 PALU - Desinta; Nashrullah; Umira H. Rusagau (STKIP Subang, 2025)
This study is classified as Classroom Action Research (CAR), meticulously designed to rigorously evaluate and enhance students’ mathematics learning outcomes through the strategic implementation of Culturally Responsive Teaching (CRT). The participants consisted of 26 second-grade students at SD Negeri 22 Palu, including 16 boys and 10 girls, whose engagement allowed a nuanced exploration of how local cultural elements can be interwoven into instructional processes. Data collection employed structured tests aimed at measuring the depth and accuracy of students’ mastery of mathematical concepts. Findings demonstrated a consistent upward trajectory from the pre-action stage to Cycle 2: 13 students (50%) achieved mastery initially, rising to 18 students (69%) in Cycle 1, and reaching 22 students (85%) in Cycle 2. Consequently, the application of CRT proved to be a pivotal strategy in strengthening mathematical understanding and significantly improving academic achievement for second-grade learners at SD Negeri 22 Palu.